Islamic Work Ethic in Mediation Influence Spirituality at Workplace, Organizational Changes, Work Ability on Organizational Commitment in Sharia Bank Employees in Medan City - Prayogi, Muhammad Andi; Asmuni, Asmuni; Nasution, Yenni Samri Juliati (IKONOMIKA, 2023)
Human resources are important things that must be maintained in a company's organization. The research approach uses an associative approach: looking at the relationship between one variable and another. The sample in this study amounted to 158 respondents, those who were employees of Islamic banking in the city of Medan. Data analysis techniques use SEM Lisrel 8.80 and the Analytical Hierarchy Process (AHP). The results of the research show that there is a direct effect of spirituality in the workplace, organizational change, and work ability on organizational commitment. There is a direct influence of spirituality in the workplace, organizational change, and work ability on the Islamic work ethic, as well as an indirect effect of spirituality in the workplace, organizational change, and work ability on organizational commitment mediated by the Islamic work ethic of employees in Islamic banking in the city of Medan, as well as the existence of a spirituality-based human resource hierarchy model that can be applied to Islamic banking in the city of Medan to be able to realize what is the goal of Islamic banking and to avoid irregularities in the process of achieving the intended goals.